IJCM_175A: Attitude towards the proposed changes by Medical Council of India (MCI) in MBBS curriculum and mandatory rural posting among medical undergraduate students - Nikhilesh R.; Aggarwal Shagun; Gupta Anubhav; Vardhan Arohi; Lonkar Aishwarya; Kumar Nithin; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: The Medical Council of India (MCI) has proposed significant changes to the MBBS curriculum, including mandatory rural postings for undergraduate medical students, to address healthcare disparities. Understanding student attitudes towards these reforms is crucial for successful implementation. Methodology: A cross-sectional study was conducted among 215 undergraduate students at Kasturba Medical College, Mangalore. Participants completed a semi-structured questionnaire assessing demographics, awareness of reforms, and attitudes towards curriculum changes and rural postings. Data were analyzed using SPSS v17.0, with perceptions measured on a 5-point Likert scale. Results: Student attitudes towards the proposed reforms were diverse. While some welcomed early clinical exposure and incentives for rural postings, others expressed concerns about implementation challenges and career implications. Family background, incentives, and perceptions of rural practice significantly influenced attitudes. Conclusion: The study underscores the complexity of student perspectives on MCI's reforms. Targeted interventions and dialogue are essential to address concerns and enhance acceptance, facilitating successful implementation.